Integrating non-viral gene therapy and 3D bioprinting for bone, cartilage and osteochondral tissue engineering - Fernandez, Tomas Gonzalez (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2017)
The repair of osteochondral defects, affecting both the articular cartilage and the underlying subchondral bone, is key for the effective recovery of joint homeostasis and the prevention of further cartilage degeneration and the onset of osteoarthritis (OA). Although important advances have been made in the field of tissue engineering to regenerate these injuries, the traditional approaches based on the formation of homogenous tissues fail to recapitulate the spatial complexity of the osteochondral unit. The objective of this thesis was to engineer a multiphasic tissue suitable for osteochondral defect regeneration by combining 3D bioprinting and non-viral gene delivery to spatially regulate the differentiation of mesenchymal stem cells (MSCs). Realising this objective first required (1) optimisation of the non-viral gene delivery vector, (2) the identification of suitable therapeutic gene combinations to direct MSC differentiation and (3) the development of printable biomaterials, also known as bioinks, which were supportive of non-viral gene delivery both in vitro and in vivo. These gene activated bioinks were capable of spatially directing MSC fate towards either the osteogenic or chondrogenic pathway. In turn, this enabled the printing of mechanically robust biphasic osteochondral constructs with zonally confined gene delivery and spatially defined stem cell differentiation and matrix deposition. In vivo, these printed constructs promoted the development of tissue mimicking key aspects of the osteochondral unit. In conclusion, this thesis highlights a promising and novel approach for the incorporation of gene delivery for 3D bioprinting and engineering of therapeutically relevant and structurally complex musculoskeletal tissues.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; PhD Trinity College Dublin, 2017